Community engagement in tuberculosis care - Syed, Lana (Henry Stewart Talks, 2024)
Tuberculosis and vulnerable populations, ENGAGE-TB, Integration of TB services with pre-existing civil society organizations, Monitoring and evaluation of TB community response outcomes, ENGAGE-TB and UK secretary-general progress report, COVID-19, WHO Civil Society Task Force on TB (CSTF-TB), The role of WHO in TB response